The Dimensions of Discipline Inventory (DDI)-Child and adoles-cent version: Analysis of the parental discipline from a gender perspective - Calvete, Esther; Gámez Guadix, Manuel; Orue, Izaskun (Anales de Psicología / Annals of Psychology, 2010)
This study translated into Spanish the Discipline Dimensions Inventory for Children (DDI-C; Straus y Fauchier, 2007) and examined gender differences in the use of discipline. The results with a sample of 1371 children and adolescents confirmed the original structure of the DDI-C, consisting of 9 factors explained by four second-order factors: Physical and psychological punishment, response cost, inductive discipline and supervision. Mothers used significantly more than fathers all types of discipline, and boys were the focus of more discipline acts than girls. Finally, fathers showed a higher implication in the discipline of sons than of daughters.